ASIAN FOOD (CARBOHYDRATE, PROTEIN, FAT) INCREASE SIMVASTATIN BIOAVAILABILITY ESPECIALLY IN MALAYSIAN SUBJECTS - ALAKHALI, KHALED. M. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Simvastatin 40 mg tablet was evaluated with Malaysian food in 9 healthy Malaysian male volunteers in a randomized, single dose, two-way crossover study. Simvastatin with Malaysian food produced higher AUC0-24, Cmax and Tmax values, as compared with fasting condition. The Ke, t1/2 and Cl did not show any significant difference between fasting and food conditions. However, food delayed gastric emptying and gastrointestinal transit, the longer gastric residence time of the simvastatin is offset by the rise in the pH of gastrointestinal tract. Food may be did not affect the increase of splanchnic hepatic blood flow by decreasing first pass metabolism of simvastatin. Food may be had the effect on the increasing of pH of gastrointestinal tract which lead to increase the stability of simvastatin in gastrointestinal fluid and its absorption into blood circulation. Key words Asian food, simvastatin bioavailabilityÂ 